Gold‐Nanoparticle‐Decorated Boron Nitride Nanosheets: Structure and Optical Properties. (6th March 2013) - Singhal, Sunil K.; Kumar, Veeresh; Stalin, K.; Choudhary, Amit; Teotia, Satish; Reddy, Gade B.; Mathur, Rakesh B.; Singh, Surinder P.; Pasricha, Renu
<x xml:space="preserve">Abstract</x> Synergetic cooperation of individual components of the nanocomposites (NCs) is responsible for their novel properties that lead to various technological applications. A simple chemical process depicting the deposition of functionalized gold nanoparticles on the surface of boron nitride nanosheets (BNNSs) in solution is reported. The structure, chemical composition, and optical properties of nanosheets are systematically studied. The deposition of Au nanoparticles on BNNS (BNNSAu) results in plasmonic band modulation, thus altering the optoelectronic properties of BNNSs. The intense surface plasmon absorption band of BNNSAu is narrowed and red‐shifted relative to the absorption band of as synthesized monometallic BNNSs. The observations reflect the strong interfacial interaction between BNNS and Au nanoparticles. This approach constitutes a basis for a simple process leading to the preparation of functionalized BNNSs and their utilization as nanoscale templates for assembly and integration with other nanoscale materials for futuristic optoelectronic devices.